2015
DOI: 10.3329/bjp.v10i3.23444
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and anti-oxidant potential of <i>Periploca hydaspidis</i>

Abstract: <p>The present study investigates antimicrobial and anti-oxidant potential of different solvent extracted samples from <em>Periploca hydaspidis </em>through disc diffusion assay. The data revealed that all the extracts reduced the growth of the tested microbes using three different concentrations. <em>Pseudomonas aeruginosa </em>and <em>E. coli</em> were sensitive to crude extracts and all fractions measuring varying degree of growth inhibition.  Similarly, the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…The fungi resistance towards the metabolites in the plant fractions might also explain the observed poor bioactivity observed with this plant remedy. These results are in agreement with similar work done by Ullah et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…The fungi resistance towards the metabolites in the plant fractions might also explain the observed poor bioactivity observed with this plant remedy. These results are in agreement with similar work done by Ullah et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…As reported elsewhere that antioxidant effect of extract/compound prevents cell damage, increases vascularity, promotes DNA synthesis and improves strength and viability of collagen fibers. Thus, the plants antioxidant effect as an individual or in combination with its rich phytochemical diversity and antimicrobial potential (Ali et al, 2018; Ullah et al, 2015) may be the possible mechanism contributing to the healing process (Bardaa et al, 2016). Furthermore, the morphometric analysis (Figure 5) is in agreement with histological findings, where treated groups displayed healed biopsies with full re‐epithelialization and well‐organized collagen fibrils without inflammatory cells.…”
Section: Resultsmentioning
confidence: 99%
“…P. hydaspidis is a leafless‐twining shrub having ever‐green smooth stems (1.5 mm diameter). Its antioxidant, antimicrobial, antiinflammatory, and hepatoprotective potential have previously been investigated (Ali et al, 2018; Ullah, Bakht, & Shafi, 2015). Owing to the antioxidant and antimicrobial efficacy of P. hydaspidis as well as the strong antimicrobial ability of silver, both of them were combined with the aim to form a more‐enhanced antimicrobial product with possible antioxidant, anticancer, and wound‐healing potential to prove as a promising alternative to currently‐used antibiotics and may further be used in phytomedicine development.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts produced from the different parts of the plants exhibit antifungal, antibacterial and insecticidal activities under lab trial as reported earlier Ullah et al, 2015). Secondary metabolites of plants with pesticidal activity are one of the best alternatives to synthetic chemicals, with least toxic effect and ecofriendly (Varma and Dubey, 1999).…”
Section: Introductionmentioning
confidence: 99%